Studies of the pharmacokinetic profile, in vivo efficacy and safety of injectable altrenogest for the suppression of oestrus in mares. Issue 7 (July 2016) - McConaghy, FF; Green, LA; Colgan, S; Morris, LH
Abstract : Objective: To investigate the efficacy and safety of the long‐acting altrenogest injection (NV Readyserve® injection) for horses. Design: A single‐dose pharmacokinetic (PK) study was conducted. The in vivo efficacy study was a blinded, repeated measures design evaluating behaviour scores. The safety study was a non‐blinded, controlled, parallel‐group, randomised‐block design as per the VICH protocol. Methods: In the PK study, serial blood samples were obtained for analysis of plasma altrenogest for 150 h following the injection and a non‐compartmental PK analysis was performed. For the efficacy study, 12 mares in oestrus were treated; they were monitored daily for 10 days for signs of oestrus during teasing and given a behaviour score that was compared with pretreatment scores. A standard safety study was conducted at 1‐, 3‐ and 5‐fold the recommended dosage for 84 days. Physical, haematological and biochemical examinations were performed. Results: Mean plasma altrenogest concentrations were greater than ≈0.5 ng/mL for 148 h following administration. Oestrous behaviour was suppressed in all mares within 24 h of administration. Two mares returned to oestrus by day 6 and the rest on days 7–10. In the safety study there were no significant differences in the physical and haematological examinations, but minor biochemical changes in muscle enzymes. There was a low incidence of injection site reactions following the 3‐ and 5‐fold dose, predominantly for pectoral injections. Conclusion: These studies support the efficacy and safety of a single dose of Readyserve® injection for the suppression of the signs of oestrus in mares for 5–7 days.